1985
DOI: 10.1136/jnnp.48.7.658
|View full text |Cite
|
Sign up to set email alerts
|

Pontine haemorrhage: a clinical analysis of 26 cases.

Abstract: SUMMARY Correlation with the size of the haematoma, neurological findings and prognosis was studied in 26 cases of hypertensive pontine haemorrhage, using CT. A good prognosis was found with no or mild disturbance of consciousness, normal pupils, and transverse diameter of the haematoma 20 mm or less. Most of the patients with poor prognosis became comatose within two hours of onset. Their pupils were dilated bilaterally, pin-point or anisocoric and the transverse diameter of the haematoma was over 20 mm.The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 6 publications
4
33
0
1
Order By: Relevance
“…Ventricular extension was only significant for mortality and hydrocephalus only for functional outcome in the univariate analysis; neither was associated with outcomes Large hematoma and severe disturbance of consciousness are commonly recognized as good predictors of mortality and unfavorable functional outcome in patients under medical treatment (3,9,10,15). It has been reported that survival is impossible if all 3 features including large paramedian pontine hemorrhage (PH), transverse diameter of hematoma ≥20 mm, and coma on admission are present in ppH patients (3).…”
Section: A B a B C D Ementioning
confidence: 91%
“…Ventricular extension was only significant for mortality and hydrocephalus only for functional outcome in the univariate analysis; neither was associated with outcomes Large hematoma and severe disturbance of consciousness are commonly recognized as good predictors of mortality and unfavorable functional outcome in patients under medical treatment (3,9,10,15). It has been reported that survival is impossible if all 3 features including large paramedian pontine hemorrhage (PH), transverse diameter of hematoma ≥20 mm, and coma on admission are present in ppH patients (3).…”
Section: A B a B C D Ementioning
confidence: 91%
“…In previous studies on pontine hemorrhage, patients harboring vascular malformations were typically excluded [6, 7, 12]or included in very small numbers [8, 11]. However, these series either predate the introduction of MRI – the only reliable noninvasive method to diagnose cavernous angiomas [14, 15]– or fail to report how often MRI was used.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of CT allowed the recognition that not only survival but also remarkable functional recovery was possible after a pontine hemorrhage [4, 5, 6, 7, 8, 9, 10]. Prognosis is highly dependent on clinical severity at presentation and the presence of certain radiological markers, such as hydrocephalus, bleeding size and extension into the midbrain and thalamus [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…5 " 1318 The transverse diameter of the hematoma has also been considered a prognostic factor. Masiyama et al 8 found a direct relation between the maximum transverse diameter of the hematoma seen in CT scans and the outcome. In their series, a diameter of < 2 0 mm was associated with favorable outcome.…”
Section: Discussionmentioning
confidence: 99%